THE USE OF FILM TO TEACH ANALYTICAL EXPOSITION WRITING - M, Musafak (ENCOUNTER, 2012)
Film certainly gives inspirations or ideas can be reproduced in written form and can be used as a teaching medium to help teachers in teaching, especially in teaching writing analytical exposition text because film performs reality of life that covers some information, ideas, and inspirations all at once. This study is aimed to find out the extent to which the teaching of writing analytical exposition text is effective with the use of film. The method of the research was an experimental study. The instruments that were used to collect the data were test as a main instrument and interview as a supporting instrument. The test was used to prove the studentsâ competence before and after the experiment was implemented. There were two kinds of test, namely pre-test and post-test, which were writing tests. The results show that the mean of writing score of experimental class (the students was taught by using films) was 81 and the mean of writing score of control class (the students was taught by text only) was 73.75. There was a significant difference in analytical exposition writingâs score between the two groups. It was showed by the mean of experimental class was higher than control class (81>73.75). On the other hand, the test of hypothesis using t-test formula showed the t-value was higher than the t-table. The score tcount was 1.85, while ttable on ï¡ = 5% with df 15 was 1.75 (1.85 > 1.75). So, the hypothesis was accepted.